Strategi Genius Learning Dalam Pembelajaran Maharatul Kitabah - Achmad Yusuf (Universitas Yudharta Pasuruan, 2019)
Arabic in learning has four language skills that must be mastered by students, namely listening skills (mahārah al-istimā '), speaking skills (mahārah al-kalām), reading (mahārah al-qirā'ah) and writing skills (mahārah al- kitābah). This conceptual study discusses the Genius Learning Strategy in Writing Skill Learning (Mahārah al-kitābah). The Genius learning strategy is a learning strategy that involves the mental and all cognitive structures of students and reconstructs and raises student experiences that have been experienced through visual, auditory, and kinesthetic student learning modalities, so that students' experiences emerge through visual, auditory and kinesthetic media. Genius learning strategies fall into the category of meaningful learning theories.